1995
DOI: 10.1111/j.1442-9993.1995.tb00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and local variation in insect herbivory, vegetation and soils of eucalypt associations in contrasted landscape positions along a climatic gradient

Abstract: Relationships with climate and local resources are developed for soils, vegetation and tree foliage as well as levels of herbivory for the dominant eucalypts at sites representing a regional gradient in climate and local contrasts in landscape position. Indicators of site productivity such as soil nitrogen and phosphorus, canopy height and cover, foliar nitrogen and water, and average leaf area tended to increase as climate became more favourable. Many were also higher in locally richer parts of the landscape.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
0
34
2
Order By: Relevance
“…Mean maximum temperature had a negative influence on foliage SLA. Previous studies Oecologia (2010) 163:437-448 443 have emphasised the impact of climate on SLA, with the majority claiming an increase in SLA with climatic favourability (Landsberg and Gillieson 1995;Medina et al 1990;Mooney et al 1978). Specific leaf area in this study varied substantially due to the unique form of the Botrycephalae bipinnate leaf in comparison to the single-bladed phyllodes presented in the other three sections.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Mean maximum temperature had a negative influence on foliage SLA. Previous studies Oecologia (2010) 163:437-448 443 have emphasised the impact of climate on SLA, with the majority claiming an increase in SLA with climatic favourability (Landsberg and Gillieson 1995;Medina et al 1990;Mooney et al 1978). Specific leaf area in this study varied substantially due to the unique form of the Botrycephalae bipinnate leaf in comparison to the single-bladed phyllodes presented in the other three sections.…”
Section: Discussionmentioning
confidence: 79%
“…The foliage properties measured follow Mooney and Gulmon (1982), Coley et al (1985), Matson et al (1994), Landsberg and Gillieson (1995) and Andrew and Hughes (2005b) to encompass a range of traits that are both sensitive to environmental constraints and differ measurably between plant species. The plants that these measurements were taken from were also used in the subsequent leaf miner and plant galler analyses.…”
Section: Plant Trait Analysismentioning
confidence: 99%
“…Both factors may be important in the D. wrightii system, because there is significant variation in the pattern of damage due to three feeding guilds both among populations within habitats (local environments) and between plant types (genotypes). Variation in resistance traits has also been documented along moisture gradients for some plant species and is hypothesized to be related to variation in the herbivore community, although cause and effect relationships may be unclear (Levin 1973;Price and Willson 1979;Louda 1983;Flanders et al 1992;Landsberg and Gillieson 1995;Hysell et al 1996). But in D. wrightii, damage inflicted by the herbivore community did not differ significantly among habitats along a moisture gradient, at least in this first year of study.…”
Section: Discussionmentioning
confidence: 82%
“…If resistance to some herbivores increases susceptibility to others (an "ecological cost", sensu Simms 1992), the relative frequencies of each herbivore may determine the frequency of resistant genotypes within populations. Herbivore communities are known to be variable both among populations and among plants within populations, thus we might expect variation in the frequency of resistance traits to reflect variation in the size and composition of the herbivore community (e.g., Levin 1973;Gibson 1979;Price and Willson 1979;Maddox and Root 1990;Landsberg and Gillieson 1995;Hysell et al 1996; reviewed by Marquis 1992).…”
Section: Introductionmentioning
confidence: 99%
“…At the regional scale the preference by greater gliders for the moister, tall eucalypt forests is also likely to reflect a productivity gradient. This incorporates not only characteristics of the substrate, such as nutrient properties, but prevailing microclimatic and topographic conditions (rainfall, solar radiation, temperature, aspect), which influence site productivity and plant growth (Kimmins et al, 1990;Landsberg and Gillieson, 1995). Landsberg and Gillieson (1995) found that at the regional scale, increased site productivity led to an increase in resource availability and vigour of eucalypts, which in turn led to an increase in the rate of insect herbivory.…”
Section: Forest Overstorey Floristic Classes and Greater Glidersmentioning
confidence: 99%